Partner Aggression among Men and Women in Substance Use Disorder Treatment: Correlates of Psychological and Physical Aggression and Injury - Chermack, Stephen T. (2008)
This study examined intimate partner aggression in a sample of 489 participants enrolled in substance use disorder treatment, and expands on prior research by including measures of various forms of aggression, a mixed gender sample (76% men, 24% women), and measurement of several potential risk domains. Aggression measures included both participant-to-partner and partner-to-participant psychological aggression, physical aggression and injury. Analyses focused on the role of distal and proximal risk factors, including demographics, history of childhood physical and sexual abuse, and family history of problems with alcohol, drugs and depression, as well as recent substance use and symptoms of depression. Overall rates of participant-to-partner psychological aggression (77%), physical aggression (54%) and injuring partners (33%) were high, as were rates of partner-to-participant psychological aggression (73%), physical aggression (51%), and injury (33%). Several distal (family history variables, physical abuse) and proximal factors (binge drinking, several different drugs, depressive symptoms) were bivariately related to most of the aggression measures. However, according to multivariate analyses predicting aggression and injury measures, binge drinking and cocaine use were the drugs significantly associated with most measures, depression symptoms also were related to most aggression and injury measures, and a history of reported childhood physical abuse was related to all frequency of aggression and injury measures among those reporting such behaviors. Overall, the high rates of aggression among both men and women observed in this study further illustrate the need for interventions targeting substance use and aggression, and for further research regarding the inter-relationships among substance, aggression and depressive symptoms.